Is Misdiagnosis of Type 1 Diabetes Mellitus in Malaysian Children a Common Phenomenon? - Mavinkurve, Meenal; Jalaludin, Muhammad Yazid; Chan, Elaine Wan Ling; Noordin, Mazidah; Samingan, Nurshadia; Leong, Annie; Zaini, Azriyanti Anuar (Frontiers in Endocrinology, 2021)
Background: Children with Type 1 diabetes (T1DM) commonly present in diabetic ketoacidosis (DKA) at initial diagnosis. This is likely due to several factors, one of which includes the propensity for T1DM to be misdiagnosed. The prevalence of misdiagnosis has been reported in non-Asian children with T1DM but not in Asian cohorts. Aim: To report the rate of misdiagnosis and its associated risk factors in Malaysian children and adolescents with T1DM. Methods: A retrospective analysis of children with T1DM below 18 years of age over a 10 year period was conducted. Results: The cohort included 119 children (53.8% female) with a mean age 8.1 SD ± 3.9 years. 38.7% of cases were misdiagnosed, of which respiratory illnesses were the most common (37.0%) misdiagnosis. The rate of misdiagnosis remained the same over the 10 year period. Among the variables examined, younger age at presentation, DKA at presentation, healthcare professional (HCP) contact and admission to the intensive care unit were significantly different between the misdiagnosed and correctly diagnosed groups (p <0.05). Conclusion: Misdiagnosis of T1DM occurs more frequently in Malaysian children <5 years of age. Misdiagnosed cases are at a higher risk of presenting in DKA with increased risk of ICU admission and more likely to have had prior HCP contact. Awareness of T1DM amongst healthcare professionals is crucial for early identification, prevention of DKA and reducing rates of misdiagnosis